ANTIMICROBIAL EFFICACY OF TWO MOUTHRINSES: AN IN VIVO STUDY - Catalina Iulia Saveanu; Forte Antonio; Dana Anistoroaei; Bamboi Irina; Lucia Barlean; Livia Bobu; Carina Balcos; Corina Cheptea; Loredana Golovcencu (Romanian Dental Association for Education, 2019)
At the individual level, behavior, education, knowledge and attitudes influence the quality of oral hygiene, diet hygiene, fluoride application, salivary flow. The aim of this study was to evaluate the efficiency of dental hygiene by chemical means in a group of students of the Dental Faculty from Iasi. Material and Method The study included 28 student subjects in the terminal year of the Faculty of Dental Medicine in Iasi. The data were recorded by clinical examination. Oral Hygiene Index (OHI) and Quigley-Hein, O'Leary, API (Aproximal Plaque Index) bacterial plaque pointers, one month after Listerine® oral rinses, and 2 months after mouthwash Oral B Pro Expert Multi-Protection (Oral B). Oral rinsing was performed as indicated by the manufacturer. The evidence of the bacterial plaque was performed with tablets of bacterial plaque disclosing. In conclusion, Listerine mounthrinse has been shown to be more effective in reducing bacterial plaque accumulation, proven by reducing OHI oral hygiene values by 0.246 and bacterial plaque scores by 8.57% compared to Oral B Pro Expert mouthwash which improved the OHI index only 0.093 and the index value of the board by 2.32%.